PENGGUNAAN METODE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMAHAMAN AYAT AL QUR’AN PADA SISWA KELAS X1 IPA 4 SMA NEGERI 4 BUKITTINGGI - Suhana Suhana (Yayasan Akrab Pekanbaru, 2018)
This study aims to obtain data and information about the implementation of Student Teams Achievement Divisions (STAD) method, to improve student learning outcomes of grade XI IPA 4, in SMA Negeri 4 Kota Bukittinggi. This research uses methods, tests and observation sheets. Understanding that happens today as energy and action in the next cycle. Data obtained then processed, to draw conclusions. Data finding after analysis after cycle 1, mean of average obtained by student 70,01 and average got value below KKM (75). Classical value was not satisfactory, then done cycle 2, the value of students with average results of students complete with an average of 76.39. Overall learning result of Islamic Education on Al Quran material about compete in class XI IPA 4 SMA Negeri 4 Bukittinggi have increased. The implication of Classroom Study Result (PTK) through cooperative learning method of Student Teams Achievement Divisions (STAD), can improve PAI learning outcomes in students of grade XI IPA 4 SMA NEGERI 4 Kota Bukittinggi. Keywords: Learning outcomes, Student Teams Achievement Divisions (STAD)